Stepwise interview with public sector - UCDA - Mr. Robert Matovu - Margiotta, S. (International Institute of Tropical Agriculture, 2019)
Interview with the regional coffee extension officer for Uganda Coffee Development Authority, Sironko district on the relationship with IITA and appreciation for the research support provided to the coffee sector.